A web based Healthcare Management System / Muhammad Farid Abdullah - Muhammad , Farid Abdullah (2001)
The project generally involved around the basic information about medical, health, drugs and diseases. This kind of information is vital yet has a very limited access. The tradition that when we get sick then we go to see doctor and ate whatever medicine that the doctor gave well, does not apply here anymore. People should know at least a simple thing about their health or medical status. They should know what they eat, what cause the illness or how to prevent it. This is possible as the system target on medical student and the public to make the system useful and helpful to them. The database section is thought the best part for the user as it gives the exact idea of possible ailment. Medical student who wants a fast accurate data on symptoms, drugs or herbs on use the database as their best platform to search for what they are looking for. So, education and knowledge are the two main keys to the existence of this project. It hopes to be a mechanism to disseminate a well informative, educative, fast and accurate data. Articles , discovery updates and medical information; and links to various informational sites are expected to help people learn be more inquisitive and educated. All the information can be access at any any time as it is online which packed with endless information from around the globe. The system also has been designed to be user-friendly system that allow user interactivity. The also are discussions on taboo issues like sexuality(child pornography) and marriage. It is to help people understand the whole concept, for not being prejudiced towards thoses issues as they have their own pros and cons. Users will be encouraged to voice out their view to make the discussion interesting and mature. This is where Forum section comes. In order to inject some consciousness to the people, morality issues on medical field also will be brought forward. The system aimed to make the public get the accurate idea and understand the right concept about the right things. Do doctor have the right to undergo euthanasia on patient that asks them to do so? Do we degrade the status of human kind by allowing human cloning? questions like these often make us think whether it's right or wrong. And there is always a room for discussion.